Aluminum chloride impaired spatial memory, but not senile plaques formation in the rat model of Alzheimer’s disease - Narwanto, Muhammad Ihwan; Rahayu, Masruroh; Soeharto, Setyawati; Nurdiana, Nurdiana (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2022)
Aluminum compounds can be easily found in the environment. Aluminum contamination is the environmental factor as one of the risk factors for Alzheimer's disease (AD). In the animal model, aluminum chloride (AlCl3) induces inflammation and oxidative stress. Inflammation and oxidative stress are important pathogenesis pathways in the AD. This study was conducted to determine whether AlCl3 can impair spatial memory and induce senile plaques formation. A total of 24 young adult Wistar rats were used in this study. The rats were divided into four groups; one control group and three AlCl3 treated groups with doses of 150 mg/kg, 300 mg/kg, and 600 mg/kg, respectively for 8 weeks. The spatial memory test was measured using Morris water maze and the histopathology was done by identification of senile plaques formation in the hippocampal tissue. Statistical analysis was performed using one-way analysis of variance (ANOVA) followed by Tukey's test for multiple comparisons. The level of statistical significance was set at a p value < 0.05. This study showed that there are significant differences (p<0,05) between the control group and all the AlCl3 treatment groups in the memory test, however, there is no change in the senile plaque’s expression in all groups. Administration of AlCl3 for 8 weeks can cause the impaired of spatial memory without senile plaques formation.